2011
DOI: 10.1111/j.1468-5965.2011.02222.x
|View full text |Cite
|
Sign up to set email alerts
|

European Union Economies Facing ‘Baumol's Disease’ within the Service Sector*

Abstract: This article analyzes the productivity of the service sector within the countries of the European Union during the period 1994-2005. After disaggregating the sector into 11 branches, the article quantifies the relative contribution of each branch to the growth of service sector aggregate productivity. The main conclusion is that the structure of the industry is increasingly dependent on those branches which have lower growth in labour productivity. This conclusion reveals that the EU service sector suffers fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…The diverging results with regard to embodied labour productivity in the production sectors in Germany and the UK highlight that it is important to go beyond the stylised division and take into account local context and complexity. This complexity has also been highlighted in other research on the topic [35,36]. The adoption of a supply-chain perspective demonstrates one aspect of this complexity, namely the interconnectedness of the different conventional sectors.…”
Section: Baumol's Cost Disease As a Barrier To The Post-growth Transimentioning
confidence: 60%
See 1 more Smart Citation
“…The diverging results with regard to embodied labour productivity in the production sectors in Germany and the UK highlight that it is important to go beyond the stylised division and take into account local context and complexity. This complexity has also been highlighted in other research on the topic [35,36]. The adoption of a supply-chain perspective demonstrates one aspect of this complexity, namely the interconnectedness of the different conventional sectors.…”
Section: Baumol's Cost Disease As a Barrier To The Post-growth Transimentioning
confidence: 60%
“…The theory of Baumol's cost disease, proposed by William Baumol and co-authors [30][31][32][33], suggests that sectors with low labour productivity growth rates face relative cost and price increases compared to sectors with high labour productivity growth rates. While Baumol's theory is highly stylised, there is considerable evidence that the processes it describes play a role in shaping the economy in the US [34], the EU [35,36], South Korea [37] and across the OECD [38,39]. While there is evidence for the existence of Baumol's theories across these countries and regions, the strength of the effect varies in line with different contexts.…”
Section: Introductionmentioning
confidence: 99%
“…The authors doubted and re-confirmed this hypothesis which has eventually become one of the fundamental bases of economics of culture [Globerman, Book (1974), Schwarz, Greenfield (1981), Heilbrun (2003), Ginsburgh, Throsby (2006)]. It is to be noted that throughout the last decade, the obvious renaissance of the Baumol's theory is observed, boundaries of its application in other sectors of economics and macroeconomic researches extend [Neck, Getzner (2007), Nordhaus (2008), Pomp, Vujic (2008), Fernandez, Palazuelo (2012)].…”
mentioning
confidence: 83%
“…This mechanism entails a rapid increase of the production costs of cultural goods relative to the increase in the price of the final product. The consequence of this economic effect, confirmed by empirical studies [4][5][6][7][8] is an objective unprofitability of cultural organizations. However, in some sources [9], the authors suggest that such mechanisms of economic modeling and productivity optimization as marketing and management, as well as the development and creation of a new paradigm of culture can overcome the "disease of inefficiency" and "cure" any "cost disease".…”
Section: Introduction: the Theoretical Landscapementioning
confidence: 91%